IMPROVING STUDENTS' VOCABULARY MASTERY THROUGH LISTENING SONG - Setiawan, Cecep (IKIP Siliwangi, 2019)
This study discusses and analyzes the use of song in improving vocabulary mastery in listening to seventh grade students’ of Mts Al-Barry Cikalong. The main concern is about the description of song implementation in the classroom and the extent which song can help students’ improve their vocabulary mastery in the listening class. Therefore, this study was conducted to investigate the progress of students’ in terms of vocabulary mastery before and after listening to songs. This study uses classroom action research method. Ideally, classroom activities and assignments that form the methodology for teaching different language skills must be designed by the teacher and must be felt by students. The researcher conducts interviews to provide information and then the results of interviews are developed and analyzed. This data is analyzed through two cycles in action. Students' vocabulary mastery ability increases, we can see from the results of cycle 1 (pre-test) before listening to English song the average score is 52.0, 62.7, 58.6 and cycle 2 (post-test) after listening to English song the average score is 71.3, 83.4, 91.4. As an end point, this research is expected to bring contribution as an alternative technique to improve vocabulary teaching in listening classes as well as to develop teacher creativity.